Patterns in COVID-19 vaccination among children aged 5-11 years in Alberta, Canada: Lessons for future vaccination campaigns - Shannon E. MacDonald; Laura Reifferscheid; Yuba Raj Paudel; Joan Robinson (Elsevier, 2024)
Objectives: In Alberta, Canada, the COVID-19 vaccination program for children aged 5-11 years was launched on November 26, 2021. Our objectives were to determine the cumulative vaccine coverage, stratified by age, during the first thirteen months of vaccine availability, and investigate factors associated with vaccine uptake. Study design: This retrospective cohort study used population-based administrative health data. Methods: We determined cumulative vaccine coverage among 5-11 year olds, stratified by year of age, during the first thirteen months of vaccine availability and used a modified Poisson regression to evaluate factors associated with vaccine uptake. Results: Of 377,103 eligible children, 44.8 % (n = 168,761) received one or more doses of COVID-19 vaccine during the study period (9.7 % received only one dose, while 35.1 % received 2 doses). Almost 90 % of initial doses were received within the first two months of vaccine availability. We found a step-wise relationship between increasing child age and higher vaccine coverage. Conclusions: Plateaued vaccine uptake indicates a need to adapt programmatic efforts to encourage parents to act on positive vaccination intentions, and reach the large contingent of parents who have reported that they remain undecided. In order to promote vaccine uptake, messaging around vaccine safety and need should be tailored to child age, rather than uniformly applied across the 5-11 year age range.